Hh/Gli antagonist in acute myeloid leukemia with CBFA2T3-GLIS2 fusion gene. Issue 1 (December 2017) - Masetti, Riccardo; Bertuccio, Salvatore; Astolfi, Annalisa; Chiarini, Francesca; Lonetti, Annalisa; Indio, Valentina; De Luca, Matilde; Bandini, Jessica; Serravalle, Salvatore; Franzoni, Monica; Pigazzi, Martina; Martelli, Alberto; et al.
Abstract Background CBFA2T3 -GLIS2 is a fusion gene found in 17% of non-Down syndrome acute megakaryoblastic leukemia (non-DS AMKL, FAB M7) and in 8% of pediatric cytogenetically normal acute myeloid leukemia (CN-AML, in association with several French-American-British (FAB) subtypes). Children with AML harboring this aberration have a poor outcome, regardless of the FAB subtype. This fusion gene drives a peculiar expression pattern and leads to overexpression of some ofHedgehog -related genes. GLI-similar protein 2 (GLIS2) is closely related to the GLI family, the final effectors of classic Hedgehog pathway. These observations lend compelling support to the application of GLI inhibitors in the treatment of AML with the aberrationCBFA2T3 -GLIS2 . GANT61 is, nowadays, the most potent inhibitor of GLI family proteins. Methods We exposed to GANT61 AML cell lines and primary cells positive and negative forCBFA2T3 -GLIS2 and analyzed the effect on cellular viability, induction of apoptosis, cell cycle, and expression profile. Results As compared to AML cells withoutGLIS2 fusion, GANT61 exposure resulted in higher sensitivity of both cell lines and primary AML cells carryingCBFA2T3 -GLIS2 to undergo apoptosis and G1 cell cycle arrest. Remarkably, gene expression studies demonstrated downregulation ofGLIS2 -specific signature genes in both treated cell lines and primary cells, in comparison with untreated cells. Moreover, chromatin immunoprecipitation analysis revealed direct regulation by GLIS2 chimeric protein ofDNMT1 andDNMT3B, two genes implicated in important epigenetic functions. Conclusions Our findings indicate that the GLI inhibitor GANT61 may be used to specifically target theCBFA2T3 -GLIS2 fusion gene in pediatric AML.